2022
DOI: 10.1111/jpc.16104
|View full text |Cite
|
Sign up to set email alerts
|

Rectal measurements and their correlation with bowel habits: Evaluation by trans‐abdominal ultrasound in children with functional constipation

Abstract: Aim Constipation is one of the most common complaints in childhood affecting the quality of life of both children and parents. This study intends to investigate rectal measurements on ultrasound and their relationship with bowel habits. Methods In this cross‐sectional study, 100 children with functional constipation (FC) referred to a single hospital between 2018 and 2019 were enrolled. After obtaining informed consent, a questionnaire including demographic and constipation characteristics was completed, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…We could only find a moderate correlation between rectal diameter and duration of symptoms, comparable to other studies. 14,17 And unlike studies performed by Pop et al 15 and Shapouri et al 8 Regression analysis to predict dilated rectal diameter also confirmed this relation; however, other parameters were not significant.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…We could only find a moderate correlation between rectal diameter and duration of symptoms, comparable to other studies. 14,17 And unlike studies performed by Pop et al 15 and Shapouri et al 8 Regression analysis to predict dilated rectal diameter also confirmed this relation; however, other parameters were not significant.…”
Section: Discussionmentioning
confidence: 56%
“…Few studies addressed a relation between age and rectal diameter. A positive correlation was specifically obvious in those studies addressing a wide age range including infants 5,8,13,15 . Karaman et al .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations